2013 Political Discussions in Foreign Affairs Committee of British Parliament on Iranian Nuclear Issue - A. A. Kornilov; N. S. Lobanova (Научный диалог)
The debate on Iran’s nuclear program in the Foreign Affairs Committee of the British Parliament, held in February 2013, in anticipation of the resumption of negotiations between Iran and the “six” of international mediators, is considered. Particular attention is paid to the position of experts invited to the meeting: representatives of academia, public organizations, military analysts. The high expert and analytical level of the meeting, which made it possible to develop effective political initiatives is noted. The most pressing issues raised during the parliamentary debates are considered. It was proved that both the deputies and the invited experts considered the further development of Tehran’s nuclear program dangerous. The authors dwell in detail on theways to resolve the Iranian nuclear problem, recommended by experts at a committee meeting: from increasing sanctions pressure to finding ways of a diplomatic settlement. The relevance of the study is due to the fact that the Iranian nuclear problem continues to be a toxic factor in the Middle East region. The novelty of the study lies in the fact that the attempt is made to reveal the position of the British Parliament members and leading experts on Iranian foreign policy. It is concluded that the political position expressed by the deputies and experts in the parliament testified to the readiness of the parties to negotiate and develop a consensus on the Iranian nuclear program.